(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study is to evaluate the effectiveness of two cycloplegic drugs used in cycloplegic refraction in hyperopic children. Study Design: Hospital based cross sectional study Place and Duration of Study: This study was carried out at the Out-patient department of Ophthalmology Dow University of Health Science (Ohja campus), Karachi Pakistan from January 2011 to June 2011. Materials and Methods: We instilled cyclopentolate 1% drops and refracted the patient followed after a few days with atropine eye drops 1% instillation and the results of both drugs were compared. The data are presented as mean and standard deviation (SD). Statistical analysis was performed using the SPSS software 19. A P-value of less than 0.05 was considered statistically significant. Results: The total refractions were recorded after cycloplegia with atropine 1% and cyclopentolate 1% eye drops. Atropine refraction (mean4.05 D) was statically insignificantly comparing with cyclopentolate refraction (mean 3.315 D; P>0.05 ) Conclusion: There is no significant difference in the cycloplegic refraction values between the two drugs hence cyclopentolate is a safe and effective drug to be used in cycloplegic refraction.